IMAGE LIFTS EXPERIENCES, NOT BONDS: EXPLAINING GEN Z LOYALTY IN THE STARBUCKS REWARDS PROGRAM - Winata, Natalia; Ludyanto, Mayfeline; Selina, Tiffanie; Tunandar, Ivana Edgina; Sanapang, Gracela Marisa (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study explains how experiential marketing and brand attachment shape Gen Z loyalty in the Starbucks Rewards Program and whether brand image strengthens these effects. We surveyed 385 Gen Z members in Makassar who had made at least two purchases in the last month and had redeemed loyalty points. Data were analyzed using variance-based structural equation modeling with PLS SEM to test direct paths and interaction terms. Results show that experiential marketing and brand attachment each have a positive and significant association with loyalty. Brand image significantly amplifies the effect of experiential marketing on loyalty,indicating that a favorable image frames and elevates how service episodes are interpreted and remembered by young consumers. In contrast, the interaction between brand image and brand attachment is not significant, corresponding to one rejected hypothesis and suggesting that attachment already operates as a deep bond that requires little image-based reinforcement. From a managerial perspective, firms should make everyday experience cues highly visible through coherent image building, while deepening attachment through recognition, access, and community within the rewards ecosystem.